2018
DOI: 10.1186/s12986-018-0318-3
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent administration of a fasting-mimicking diet intervenes in diabetes progression, restores β cells and reconstructs gut microbiota in mice

Abstract: Fasting and especially intermittent fasting have been shown to be an effective intervention in many diseases, such as obesity and diabetes. The fasting-mimicking diet (FMD) has recently been found to ameliorate metabolic disorders. To investigate the effect of a new type of low-protein low-carbohydrate FMD on diabetes, we tested an FMD in db/db mice, a genetic model of type 2 diabetes. The diet was administered every other week for a total of 8 weeks. The intermittent FMD normalized blood glucose levels in db/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 41 publications
6
75
0
1
Order By: Relevance
“…One of the most intriguing findings was the increased abundance of Parabacteroides distasonis species. This taxonomic group has been recently associated with improved insulin sensitivity in obese human subjects [ 28 ], alleviated obesity and metabolic dysfunctions in mice [ 29 ], and has been proven to negatively correlate with fasting blood glucose levels [ 30 ]. In addition, some recent studies of metformin effects have observed an increase in the abundance of this species or obtained associations with therapy outcomes [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most intriguing findings was the increased abundance of Parabacteroides distasonis species. This taxonomic group has been recently associated with improved insulin sensitivity in obese human subjects [ 28 ], alleviated obesity and metabolic dysfunctions in mice [ 29 ], and has been proven to negatively correlate with fasting blood glucose levels [ 30 ]. In addition, some recent studies of metformin effects have observed an increase in the abundance of this species or obtained associations with therapy outcomes [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these bacteria, including Parabacteroides, Megasphaera, Ruminococcaceae UCG 005, Ruminococcaceae UCG 002, Eubacterium xylanophilum group and Eubacterium eligens group, could produce short-chain fatty acids (SCFAs) such as butyrate, propionate, and acetate (Chen et al, 2017;Chung et al, 2017;Gao et al, 2018;Wang et al, 2018bWang et al, , 2019Metzler-Zebeli et al, 2019), which could maintain normal physiological functioning of the intestines, regulate gut permeability, increase insulin sensitivity, and induce gut inflammatory responses that recede the development of diabetes (Vaarala et al, 2008). Additionally, the study provided a clear insight into the correlations between differential genera and maternal clinical indices, besides several reported associations (Guo et al, 2018;Wei et al, 2018), the others, especially the associations with blood pressure, blood lipids, dietary intake, liver and kidney functions, still need validation via continued research in this field. Moreover, studies regarding the potential causal links between the collective effects of gut microbiota and their relationship to GDM are also warranted.…”
Section: Alterations In Gut Microbial Composition and Functional Annomentioning
confidence: 99%
“…Moreover, various studies in type 2 diabetic mice showed that IF regimen could stimulate the enrichment of species of the genera Lactobacillus [103,104], Oscillospira [103], and Ruminococcus [103] and the reduction of A. muciniphila [103], Bacteroides [103], Bifidobacterium [103], Enterococcus [104], and Streptococcus [104], compared with ad libitum feeding. Furthermore, compared with control mice, FMD-diabetic mice showed an increase of Parabacteroides and Blautia abundances and reduced counts of Prevotellaceae, Alistipes and Ruminococcaceae [15].…”
Section: Fasting and Gut Microbiota Variationsmentioning
confidence: 91%
“…The most studied schedules are (i) time-restricted feeding (TRF) which provides food intake in a 4-to 12-h time window, (ii) intermittent fasting (IF) which provides an alternation of 24-h fasting (or very low calories, corresponding to 25% of energy needs) with a 24-h ad libitum eating period, and (iii) fasting-mimicking diet (FMD) proposing a reduction of caloric intake for five consecutive days, through a low-caloric vegetable-based diet, before returning to normal eating cycles once a month. Many studies suggest promising beneficial health effects by performing these strategies, such as the delay of the onset of chronic diseases in selected patients [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%